A history of women in America - Coryell, Janet L. 1955-; Faires, Nora Helen (New York, NY McGraw-Hill, 2012)
A History of Women in America integrates the stories of women in America into the national narrative of American history. By weaving women's lives into the heart of the country's narratives, readers will see women where they were, rather than having them appear as appendages to events controlled largely by men. Coryell and Faires use accessible language, telling stories that will attract beginning scholars to the field of history. Major ethnic groups are incorporated, from Native American and African women who appear earliest in the text, to the major immigrant groups, such as Hispanic, Latina, Chicana, and Asian women, who occupy increasingly larger roles throughout the nineteenth and twentieth centuries.
Native women and European encounters -- Women colonists in seventeenth-century English America -- From colonies to nation: the eighteenth century -- Women in the new nation -- Rights contested -- Reconstruction, resistance and reform -- New century, new woman -- Good times, hard times, wartime -- Cold war, warm hearth -- Feminism and ferment -- Backlash and the third wave -- Epilogue: The contemporary era.
Includes bibliographical references and index.
Keywords: Women -- United States -- History